Erratum: An unnoticed origin of fever: Periapical tooth abscess - Three case reports and literature review - Arslan, Ferhat; Karagöz, Ergenekon; Yiğit Arslan, Birsen; Mert, Ali (NLM (Medline), 2017)
Erratum Following publication of the Original article An unnoticed origin of fever: Periapical tooth abscess - Three case reports and literature review (Infez. Med., volume 24, issue 1, pages 67-70, year 2016) We became aware that some authors were missing from the title page The correct list of the authors and affiliations is the following An unnoticed origin of fever: Periapical tooth abscess - Three case reports and literature review Ferhat Arslan1, Ergenekon Karagöz2, Mesut Yilmaz1, Ayse Batirel3, Birsen Yigit Arslan4, Nedim Ozer5, Nadir Alpay6, Ali Mert1 1Department of Infectious Diseases and Clinical Microbiology, Istanbul Medipol University Hospital, Istanbul, Turkey 2Department of Infectious Diseases and Clinical Microbiology, Van Military Hospital, Van, Turkey 3Department of Infectious Diseases and Clinical Microbiology, Lutfi Kirdar Training and Research Hospital, Istanbul, Turkey 4Department of Anesthesiology and Reanimation, Esenyurt State Hospital, Istanbul, Turkey 5Department of Dentistry, Istanbul Medipol University Hospital, Istanbul, Turkey 6Department of Internal Medicine, Istanbul Medipol University Hospital, Istanbul, Turkey.
Keywords: Tooth Abscess; Periapical; Case Reports